SERVQUAL outpatient service quality and patient satisfaction: policy implications at Puskesmas Kabanjahe - Sirajuddin, Inayyah Nur Fitry; Istiqamah, Nurul Fajriah; Islamiati, Sarifah Dwi; Rachman, Hervien Maulana (Talenta Publisher, 2026)
Patient satisfaction is a crucial indicator of healthcare service quality. Puskesmas Kabanjahe, serving 64,890 residents across 10 villages, requires comprehensive evaluation of outpatient service quality to inform policy improvements and achieve the mandated 95% satisfaction threshold. This study evaluated the relationship between SERVQUAL dimensions (reliability, responsiveness, assurance, empathy, and tangibles) and patient satisfaction at Puskesmas Kabanjahe to provide evidence-based policy recommendations. A cross-sectional study was conducted from April to August 2025 involving 237 outpatient visitors selected through accidental sampling. Data were collected using structured SERVQUAL questionnaires on a five-point Likert scale and analyzed using Spearman rank correlation. All five SERVQUAL dimensions demonstrated statistically significant relationships with patient satisfaction (p<0.05). Descriptively, all five dimensions were rated as good by the majority of respondents: tangibles (99.6%), assurance (99.2%), reliability (98.7%), responsiveness (98.3%), and empathy (98.3%). Spearman correlation analysis confirmed significant positive relationships between each dimension and patient satisfaction (rs= 0.134–0.212; p<0.05 for all dimensions), with reliability showing the strongest correlation (rs=0.212). Female respondents exhibited significantly higher satisfaction (91.7%) compared to males (80.6%) (p=0.04). Occupation showed borderline significance (p=0.05), with farmers demonstrating lowest satisfaction (87.5%). These findings confirm that outpatient services at Puskesmas Kabanjahe have achieved high service quality consistent with SPM requirements, while highlighting the need for targeted improvements in specific demographic groups to ensure equitable attainment of the mandated 95% satisfaction threshold across all patient populations.